SIMULASI DAN PERBANDINGAN KINERJA OSPF DAN EIGRP PADA TOPOLOGI HYBRID (STAR DAN MESH) DI CISCO PACKET TRACER - Naibaho, Marcel; Sirait, Juan Sebastian; Tambunan, Yosua; Situmorang, Yudi Yohannes; Limbeng, Yuni br; Sipayung, Sardo Pardingotan (Politeknik META Industri Cikarang, 2025)
This research discusses the simulation and comparison of OSPF and EIGRP performance on hybrid topology (star and mesh) in Cisco Packet Tracer. The main objective of this research is to compare delivery time and routing efficiency on the performance of OSPF and EIGRP routing protocols on hybrid network topologies (star and mesh) using Cisco Packet Tracer. The research was conducted by dividing the IP address on each network and simulating data transmission with sizes of 400 bits, 800 bits, and 1200 bits. The results of this study show the comparison of the difference in delivery time between OSPF and EIGRP protocols is 0.0026 seconds with a packet size of 400 bits, 0.003 seconds with a packet size of 800 bits and 0.00317 seconds with a packet size of 1200 bits with EIGRP is superior to OSPF with a ratio of 3:0. With these results, EIGRP performance is slightly better than OSPF performance in terms of delivery time.